2021
DOI: 10.1016/j.heliyon.2021.e07153
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genetic modifiers of lifespan on a high sugar diet in the Drosophila Genetic Reference Panel

Abstract: Genome-wide association studies (GWAS) have become beneficial in identifying genetic variants underlying susceptibility to various complex diseases and conditions, including obesity. Utilizing the Drosophila Genetic Reference Panel (DGRP), we performed a GWAS of lifespan of 193 genetically distinct lines on a high sugar diet (HSD). The DGRP analysis pipeline determined the most significant lifespan associated polymorphisms were within loci of genes involved in: neural processes, behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…The biological functions of olf413 have been little studied. It has been identified as an associated gene in a few GWA analysis studies carried out for psychostimulant drug preferences [ 15 ] and dietary dependent reduction in life span and starvation resistance [ 16 , 17 ]. Recently studies have shown food preference, feeding and motor activity defects in olf413 mutant adults [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The biological functions of olf413 have been little studied. It has been identified as an associated gene in a few GWA analysis studies carried out for psychostimulant drug preferences [ 15 ] and dietary dependent reduction in life span and starvation resistance [ 16 , 17 ]. Recently studies have shown food preference, feeding and motor activity defects in olf413 mutant adults [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gene olf413, annotated as CG12673 has been predicted to code for a protein paralogous to Tβh having a role as an enzyme in octopamine biogenesis [14]. Biological function of olf413 has been very little worked out, except in a few genome-wide association (GWA) screens, food preference and motor behavior analysis [15][16][17][18][19]. This study shows that olf413 mutants have decreased octopamine levels and the loss of function mutant embryos show severe disruptions in motor nerves of ventral nerve cord (VNC) and their peripheral motor axon projections.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the existence of linkage among genome sites, correction methods such as Bonferroni or Benjamini-Hochberg FDR that assume independence among detected variants are overly stringent and can result in a high number of false negatives [57,58]. Here, we used a p < 10 -5 cut-off, without FDR correction, that is commonly applied in GWAS using DGRP lines [59][60][61]. We found 22 variants with effects on expression of SP and 8 variants with effects on Acp36DE expression (electronic supplementary material, table S6, figure 3).…”
Section: (D) Gwas Identifies a Predominant Role Of Cis-regulatory Pol...mentioning
confidence: 99%